2022
DOI: 10.1128/jvi.00356-22
|View full text |Cite
|
Sign up to set email alerts
|

Movements of Ancient Human Endogenous Retroviruses Detected in SOX2-Expressing Cells

Abstract: Human endogenous retroviruses (HERVs) account for approximately 8% of the human genome; however, the physiological role of HERV-K remains unknown. This study found that HERV-K LTR5Hs and LTR5B were transactivated by SOX2, which is essential for maintaining and reestablishing pluripotency.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 66 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…S1D ). Recently, it was reported that SOX2, an important marker of initialization and pluripotency in undifferentiated cells, induces genome expression in human endogenous retroviruses (HERVs) [ 26 ]. We investigated the initialization state of iPSCs by analysing expression of HERVs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S1D ). Recently, it was reported that SOX2, an important marker of initialization and pluripotency in undifferentiated cells, induces genome expression in human endogenous retroviruses (HERVs) [ 26 ]. We investigated the initialization state of iPSCs by analysing expression of HERVs.…”
Section: Resultsmentioning
confidence: 99%
“…The primers for human OCT3/4, human NANOG, human SOX2, human β-actin, human integrin α1, human integrin α5, human integrin α6, human integrin αV, human integrin β1, human integrin β3, human integrin β4 and human CDH1 and human GAPDH were designed using the Primer 3 Plus application ( http://www.bioinformatics.nl/cgi-bin/primer3plus/primer3plus.cgi ). The primer sequence for HERV-K Gag CA was selected from the sequence described in a previous paper [ 26 ]. Other primers were purchased from Takara Bio Inc. (Shiga, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Transcription factor binding sites (TFBSs) have been observed in association with HERVs and LTRs, regulating the transcriptional activity of these exogenous elements ( Monde et al, 2022 ; Liu et al, 2022 ). In order to determine the transcription factors (TFs) associated exclusively with ERVs, we excluded all the TFBSs shared by orthologs and paralogs annotated in structural equivalent sections.…”
Section: Resultsmentioning
confidence: 99%
“…Another interesting question related to the transcription factor analysis is whether the transcription factor binding sites can activate or deactivate ERVs ( Grow et al, 2015 ; Monde et al, 2022 ). A frequent target of ERV silencing is the so-called primer binding site (PBS), although there are other described mechanisms associated with this process.…”
Section: Discussionmentioning
confidence: 99%
“…HERVs are flanked by two long terminal repeats (LTRs) that contain the regulation part of the retrovirus. However, most HERVs are present as solo LTRs [ 46 ]. The most studied HERV group is the W group, which is specifically mobilized by the LINE-1 machinery [ 43 ].…”
Section: Endogenous Viral Elementsmentioning
confidence: 99%